Radial force control of multi-sector permanent magnet machines for vibration suppression - Valente, G.; Papini, Luca; Formentini, Andrea; Gerada, C.; Zanchetta, Pericle (Institute of Electrical and Electronics Engineers, 2018)
Radial force control in electrical machines has been widely investigated for a variety of bearingless machines, as well as for the conventional structures featuring mechanical bearings. This paper takes advantage of the spatial distribution of the winding sets within the stator structure in a multisector permanent-magnet (MSPM) machine toward achieving a controllable radial force. An alternative force control technique for MSPM machines is presented. The mathematical model of the machine and the theoretical investigation of the force production principle are provided. A novel force control methodology based on the minimization of the copper losses is described and adopted to calculate the d–q axis current references. The predicted performances of the considered machine are benchmarked against finite-element analysis. The experimental validation of the proposed control strategy is presented, focusing on the suppression of selected vibration frequencies for different rotational speeds.